2018
DOI: 10.1103/physrevb.97.121107
|View full text |Cite
|
Sign up to set email alerts
|

Antiphase Fermi-surface modulations accompanying displacement excitation in a parent compound of iron-based superconductors

Abstract: We investigate the transient electronic structure of BaFe2As2, a parent compound of iron-based superconductors, by time-and angle-resolved photoemission spectroscopy. In order to probe the entire Brillouin zone, we utilize extreme ultraviolet photons and observe photoemission intensity oscillation with the frequency of the A1g phonon which is antiphase between the zone-centered hole Fermi surfaces (FSs) and zone-cornered electron FSs. We attribute the antiphase behavior to the warping in one of the zone-center… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This behavior is reminiscent of anti-phase oscillations reported in Bi 2 Te 3 [6] and BaFe 2 As 2 [30]. The present finding differs in that the pivoting occurs at a seemingly arbitrary k-point, and is not associated with high-symmetry directions in the Brillouin zone.…”
supporting
confidence: 65%
“…This behavior is reminiscent of anti-phase oscillations reported in Bi 2 Te 3 [6] and BaFe 2 As 2 [30]. The present finding differs in that the pivoting occurs at a seemingly arbitrary k-point, and is not associated with high-symmetry directions in the Brillouin zone.…”
supporting
confidence: 65%
“…Recently, coherent phonon excitations coupled to the electronic Higgs mode has been found by the pump-probe optical measurements with the similar pump fluence to our TARPES measurements for Ta2NiSe5 14 . Also, an interesting relation between the observed coherent phonon excitations and temperature-dependent Raman spectra has been reported by Mor et al 16 The coherent phonon excitations observed in various systems [25][26][27] are most likely explained by the displacive excitation of coherent phonons (DECP) mechanism 28 . In this mechanism, the adiabatic energy potential is modified due to photo-excitations and has the minimum with the finite atomic displacements corresponding to the Ag phonon.…”
Section: Discussionmentioning
confidence: 83%
“…The observed anti-phase oscillation of k F x and k F y directly represents the Pomeranchuk-type oscillation of Fermi surface 29 , being intensively discussed as the fundamental excitation in the electronic nematic state. The time scale of the oscillatory response (1.4 ps, 3.1 meV) is considerably slow as compared to the coherent A 1g optical phonon (190 fs, 22 meV), which is known to strongly couple to the electronic state in this system 2527 . Their possible interplay is unfortunately hidden in the present TARPES data, possibly due to the duration of the pump pulse (170 fs) comparable to the time period of A 1g mode (190 fs) that tends to vanish the coherent oscillation.…”
Section: Resultsmentioning
confidence: 95%
“…Time-resolved ARPES (TARPES) has the potential impact to resolve electron dynamics not only in energy and momentum but also into spin and orbital degrees of freedom. A wide range of materials have been investigated for clarifying their electronic dynamics, such as the recombination of the superconducting quasiparticles 21,22 , fluctuating charge density waves 23 , collapse of long-range order 24,25 , and coupling with optical phonons 2527 . These results, which are inaccessible from equilibrium state, contributed to the deeper understanding of exotic quantum states, especially those with short lifetimes.…”
Section: Introductionmentioning
confidence: 99%